Postmortem biochemistry: Current perspectives and the road ahead - Singh Shekhawat, Raghvendra; Meshram, Vikas; Kanchan, Tanuj (Journal of Indian Academy of Forensic Medicine, 2021)
Thanato-biochemistry or postmortem biochemistry is a  comprehensive speciality study of biochemistry in which fluids  and tissues retrieved from the human corpse are subjected to  qualitative and quantitative estimation of desirable biochemical  parameters. The field of postmortem biochemistry has started  evolving in the last few decades. The conventional autopsy  practice relies on the morphological findings observed during  necropsy. At many occasions, the aid of pathology and forensic  science laboratories is taken for histochemical examination and  chemical analysis, respectively. The analysis of the biochemical  parameters from the post mortem body samples can offer  intensive help in assessing the derangements in the functional,  biological and molecular parameters, which are not observed in  the traditional method of autopsy conduction.
Keywords: Postmortem; biochemistry; road